Curcumin enhances bedaquiline’s efficacy against Mycobacterium abscessus: in vitro and in vivo evidence - Dan Luo; Weile Xie; Zhe Wang (Microbiology Spectrum)
ABSTRACT In this study, we describe the combined effects of bedaquiline (BDQ) and the natural product curcumin (CUR) on Mycobacterium abscessus. In both in vitro and in vivo experiments, CUR enhanced BDQ’s inhibitory effect. This combination reduced M. abscessus survival under nutrient-deprived, hypoxic, and acidic conditions, accelerated ATP depletion, mitigated BDQ-induced respiratory compensation, and effectively improved infection outcomes in both normal and immunosuppressed mice. Metabolomics analysis revealed that adding CUR to BDQ exacerbated BDQ-dependent downregulation of purine and pyrimidine metabolism and amino acid synthesis. Thus, BDQ-CUR combination therapy could potentially be applied to treat M. abscessus infections.IMPORTANCEMycobacterium abscessus is an emerging pathogen that causes pulmonary infections, particularly in immunocompromised patients. It exhibits natural resistance to many anti-tuberculosis drugs, posing significant challenges for both patients and physicians, thereby raising the need for innovative drug discovery. Here, we describe the combined effects of bedaquiline (BDQ) and curcumin (CUR) on M. abscessus. In vitro and in vivo studies have shown that CUR enhances the inhibitory effect of BDQ. Additionally, we investigated the synergistic effects at the metabolic level. Thus, these findings highlight the potential of BDQ-CUR combination therapy against M. abscessus infections.